2005
DOI: 10.1021/bi048142j
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Communication between the Regulatory and Catalytic Domains of a Protein Tyrosine Kinase, Csk

Abstract: Protein tyrosine kinases (PTKs) are important regulators of mammalian cell function and their own activities are tightly regulated. Underlying their tight regulation, all PTKs contain multiple regulatory domains in addition to a catalytic domain. C-terminal Src kinase (Csk) contains a catalytic domain and a regulatory region, consisting of an SH3 and an SH2 domain. In this study, we probed the communication between the regulatory and catalytic domains of Csk. First, kinetic characterization of SH3 and SH2 doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 33 publications
4
38
0
Order By: Relevance
“…Thus, remote docking interactions are likely a key part of the recognition mechanism. Our previous studies determined that Csk recognition of Src was not dependent on the Csk SH2 or SH3 domains (24); rather, Csk contained a substrate-docking site located in the peptide-binding lobe, centered on the ␣-helix D (15). In the current study, we identified several residues in the ␣-helix J of Src as the docking determinants recognized by the Csk substrate-docking site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, remote docking interactions are likely a key part of the recognition mechanism. Our previous studies determined that Csk recognition of Src was not dependent on the Csk SH2 or SH3 domains (24); rather, Csk contained a substrate-docking site located in the peptide-binding lobe, centered on the ␣-helix D (15). In the current study, we identified several residues in the ␣-helix J of Src as the docking determinants recognized by the Csk substrate-docking site.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, any factors that affect the catalytic activity of Csk could potentially affect Csk-Src recognition, even if such factors do not directly affect the physical interaction between Csk and Src. For example, Csk catalytic activity is positively regulated by the presence of its SH3 and SH2 domains (24) and the SH2 domain ligand (26). Such regulations could potentially affect the substrate recognition as well.…”
Section: Discussionmentioning
confidence: 99%
“…2A) (LaFevre-Bernt et al 1998;Hawkins and Marcy 2001;Guo et al 2006;Joseph et al 2007b). Mutation of a well-conserved tryptophan residue in the Itk and Btk SH2-kinase linkers (W355 in Itk, W395 in Btk) results in a significant decrease in kinase activity (Lin et al 2005;Guo et al 2006;Joseph et al 2007b) whereas mutation of the corresponding tryptophan in the Src kinase Hck leads to a dramatic increase in the activity of that kinase (LaFevre-Bernt et al 1998). In this regard, Itk is similar to Csk (carboxy-terminal Src kinase), another tyrosine kinase comprised of the common SH3-SH2-Kinase cassette and regulated in a manner opposite that of Src (Huang et al 2009).…”
Section: Regulation Of Itk Activitymentioning
confidence: 99%
“…[11] Since the SH2 domain is critical for maintaining efficient catalysis in Csk, [10,18] we wondered whether the oxidation state of the SH2 domain could influence strain energies within the Csk structure and, thus, provide theoretical grounds for understanding the effects of reducing agents on catalytic activity. To address this issue, we compared the normal modes and associated strain energies for Csk, both with and without disulfide bond formation between Cys122 and Cys164.…”
Section: Communication Between the Disulfide Bond And The Active Sitementioning
confidence: 99%